Identity and Social Reconciliation in a Postconflict Korea: What Role for the Church? - Son, Sarah A. (International bulletin of mission research, 2018)
One of the greatest tragedies of the inter-Korean conflict is the loss of shared identity between the two peoples. If the situation arises that the two nations have the opportunity to become one again, building a shared sense of collective identity will be the primary task of a unified administration. As the experiences of other countries show, navigating a political transition involves both dealing with the past and building a vision for the future that provides a sense of national solidarity and hope; the church has a key role to play in facilitating reconciliation and long-term peace.